Regional Security Community in the Western Balkans: A Cross-Comparative Analysis - Cruise, Rebecca J.; Grillot, Suzette R. (Journal of Regional Security, 2018)
Many have observed the early phases of regional security community development in the Western Balkans over the past decade. Much of this research has focuses on elite-level, government to government and government to International Organization cooperation. Yet, for security community to become a reality, it must also develop at the public-level. In the Western Balkans, it remains to be seen just how deep this new sense of community reaches. Based on fieldwork and surveys conducted in 2007 and 2008, a crucial moment for the region, we argue that public-level security community is inconsistent and in some areas is all together lacking. It is our position that programs advanced in the Western Balkans must concentrate not just on elite institution building, but also on community building within and between the individual countries of the region.